Effect of sericin coating on reducing browning of fresh-cut mango cv. ‘Nam Dok Mai No. 4’ - Chimvaree, Chalida; Wongs-Aree, Chalermchai; Supapvanich, Suriyan; Charoenrat, Theppanya; Tepsorn, Racha; Boonyaritthongchai, Panida (Agriculture and Natural Resources, 2019)
The effects were investigated of a sericin-based edible coating on the browning inhibition of fresh-cut ‘Nam Dok Mai No.4’ mango during storage. Mango fruits were cut in the longitudinal direction and cross-sectional direction and then these fresh-cut mangos were dipped in sericin solution or distilled water (control) and samples were placed in a rigid-plastic box and stored at 10°C to accelerate browning. The results showed that the sericin-coated fruit samples had lower browning scores, browning index and enzymatic browning activity compared to the control set. Fresh-cut mango coated with sericin solution had higher L* color values than the control. The hue angle and chroma values of samples treated with sericin remained constant while non-treated fruit had gradual decreases during storage. The sericin treatment also decreased the browning enzymatic activities of polyphenol oxidase, peroxidase, phenylalanine ammonialyase and the phenolic content. On the other hand, there was no significant difference in the firmness and ascorbic content between the treatment and control sets. Sericin-treated mango had a storage life of 3 d while the control set had a storage life of 1 d.